Trends in the use of non-nutritive sweeteners among female university students in the United Arab Emirates - Dalia Haroun; Aseel Ehsanallah; Wafa Mubarak (Preventive Medicine Reports)
Objective: This study aimed to explore the consumption patterns of non-nutritive sweeteners (NNS) among female university students in the United Arab Emirates (UAE), in the context of rising health awareness. Methods: A cross-sectional survey was conducted from February to April 2023 among female university students in the UAE. A total of 192 participants aged 18 and above were recruited through convenience sampling. A structured, self-administered online questionnaire was used to collect data on NNS consumption, motivations for use, physical activity, dietary habits, and self-reported height and weight. Body Mass Index (BMI) was calculated and categorized using the World Health Organization (WHO) criteria. Data were analyzed using SPSS version 22.0. Descriptive statistics and chi-squared tests were applied, with significance set at p < 0.05. Results: Only 24 % of participants reported current consumption of artificially sweetened foods and beverages, while 15.1 % used sweeteners in pill or powder form. The most common reasons for using NNS were weight management and adopting a healthy diet. Among former users, taste preferences (23.9 %) and perceived health risks (13 %) were primary reasons for discontinuation. Significant associations were observed between NNS use and BMI, engagement in weight loss diets, and physical activity levels. Conclusions: NNS consumption appears relatively low among female university students in the UAE, with health-driven motivations and sensory preferences shaping usage patterns. These findings highlight the need for targeted public health messaging and suggest potential shifts in dietary behavior among young women.